Understanding dust sources through remote sensing: Making a case for CubeSats - Baddock, Matthew; Dominguez Acosta, Miguel (2020)
Abstract: Dust sources have been revealed through remote sensing, first regionally by ~1° resolution sensors (TOMS), then at sub-basin scale by moderate-resolution sensors (MODIS). Sensors with higher spatial resolution until recently were poorly temporally-resolved, precluding their use for systematic investigations of sources. Now, “CubeSat” constellations with high-temporal-and-spatial-resolution sensors such as PlanetScope offer ~3 m resolution and daily (to sub-daily) temporal resolution. We illustrate the spatio-temporal dust plume observation capabilities of CubeSat data through a dust event case study, Bolson de los Muertos playa, Chihuahuan Desert, Mexico. For the event, PlanetScope showed numerous discrete point sources, revealing variability of surface erodibility and emission over ~8% of a focus area at time of capture. The unprecedented detail of PlanetScope imagery revealed plume development where outer-playa sands and fluvial-deltaic inputs contact lacustrine silts/clays, consistent with field-studies. PlanetScope's high fidelity improves spatial quantification and temporal constraint of source activity, and we assess the spatio-temporal capabilities of CubeSat in context with other dust observation remote sensing systems. Compared to previous satellite technologies, CubeSats bring better potential to link remote sensing to field observations of emission. This leap forward in the remote sensing of dust sources calls for the systematic analysis of CubeSat imagery in source areas.